2016
DOI: 10.4142/jvs.2016.17.3.421
|View full text |Cite
|
Sign up to set email alerts
|

Uracil-DNA glycosylase-treated reverse transcription loop-mediated isothermal amplification for rapid detection of avian influenza virus preventing carry-over contamination

Abstract: Here, we describe a uracil-DNA glycosylase (UNG)-treated reverse transcription loop-mediated isothermal amplification (uRT-LAMP) for the visual detection of all subtypes of avian influenza A virus (AIV). The uRT-LAMP assay can prevent unwanted amplification by carryover contamination of the previously amplified DNA, although the detection limit of the uRT-LAMP assay is 10-fold lower than that of the RT-LAMP without a UNG treatment. To the best of our knowledge, this is the first successful application of deoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…While establishing the assay, we noted susceptibility to contamination that was easily addressed by the standard precautions used to prevent template carryover for any nucleic acid amplification test, such as physical separation of mastermix preparation from sample inoculation; not opening post-amplification reaction tubes or plates; and inclusion of negative extraction controls. Addition of uracil-N-glycosylase has been reported as a strategy to limit the risk of amplicon contamination, however this is associated with a loss of detection sensitivity [36].…”
Section: Discussionmentioning
confidence: 99%
“…While establishing the assay, we noted susceptibility to contamination that was easily addressed by the standard precautions used to prevent template carryover for any nucleic acid amplification test, such as physical separation of mastermix preparation from sample inoculation; not opening post-amplification reaction tubes or plates; and inclusion of negative extraction controls. Addition of uracil-N-glycosylase has been reported as a strategy to limit the risk of amplicon contamination, however this is associated with a loss of detection sensitivity [36].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we tested the addition of deoxyuridine triphosphate (dUTP) and uracil DNA glycosylase (UDG) to prevent carry-over contamination using recommended UTP/UDG concentrations [ 31 , 32 ]. We found that these additives had no effect on reaction speed or sensitivity but increased the specificity (fewer false positives), so we therefore incorporated the UTP/UDG system into subsequent experiments ( Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…leprae RLEP. We also used UNG in STNPCR, and the UNG-treated loop-mediated isothermal amplification (LAMP) assay can prevent unwanted amplification by carryover contamination of the previously amplified DNA [26]. The STNPCR and SYBRGreen PCR assays were optimized to minimize the duration of the PCR protocol (2 h and 1 h, respectively) and can detect even low levels of template (13 fg) genomic DNA.…”
Section: Discussionmentioning
confidence: 99%